The competent authority to resolve the conflicts of jurisdiction between the administrative and ordinary courts in Iraq - مهدي مروة موفق; جعفر رشا محمد (Journal of Legal Sciences, 2021)
Jurisdictional conflict is legally concerned with the dispute between two judicial bodies concerning the consideration of a specific subject, such as the dispute between the ordinary judiciary and the administrative judiciary in the countries that adopt the dual justice system. The dispute also takes place between two courts that have a single judicial system، Among them, there may also be a conflict in the countries that adopt the federal systemو، which is a manifestation of the bilateral judicial system, which is one of the most important reasons for conflict of jurisdiction in the federal states. It is known that Iraq has become a double jurisdiction by the issuance of Law No. (106) 1989 Second Amendment to the law of the State Council No. 65 of 1979, the federal system adopted under the law of the State Administration for the transitional period in 2004 and the 2005 Constitution Therefore, the legislator, through the experiences of the countries that adopt the dual justice system, has taken into account the possibility of conflict of jurisdiction between the two sides of the ordinary judiciary and the administrative judiciary. The task of adjudicating it to a body that appoints the authority and granting the Supreme Administrative Court the jurisdiction of the Administrative Court and the Staff Court. Jurisdiction in the conflict of jurisdiction between the federal judiciary and the judiciary in the region to the Federal Supreme Court، where it pointed out its competence in adjudicating the conflict of jurisdiction between the federal judiciary and the judicial bodies of the regions and governorates not organized in the province and the separation in the conflict of jurisdiction Between the judicial bodies of the district or the governorates that are not organized in a province. This research highlights the types of conflict of jurisdiction in Iraq and the competent authority to solve it through the analysis of the legal texts and decisions related to the subject.